Efectos de un programa de entrenamiento multicomponente en pacientes con Parkinson. - Gazmuri Cancino, Marcela; Regalado Vásquez, Érica; Pavez-Adasme, Gustavo; Hernández-Mosqueira, Claudio
Background: Multicomponent physical training in patients with Parkinson disease may improve their functional independence, especially in terms of gait speed and coordination. Aim: To assess the effects of an eight weeks multicomponent physical training program in patients with Parkinson disease. Material and methods: Fourteen patients with Parkinson disease participated in a physical training program that lasted eight weeks. Three sessions lasting 60 minutes per week were carried out. Patients were assessed using the six minutes walk, timed up and go and the unipodal stance test. Results: After the training period, significant improvements in the six minute walk test and timed up and go were observed. No significant changes were observed in the unipodal stance test. Conclusions: The eight weeks training program improved gait speed and functional status in these patients with Parkinson disease.